(untitled) (Human Factors in Design, 2024)
The study proposes to identify the main demands faced by the head of the urgency and emergency unit of a university hospital in Santa Catarina, focusing on the ergonomics of the activity. The intention is to propose ergonomic recommendations for the work process, since there is a lack of studies that analyze the work of health professionals who work in strategic leadership positions. The research method was content analysis, through semi-structured interviews. Adaptation of the activities developed was proposed, in the organization of work, distribution of tasks, training and qualification of the team, among other strategies to promote a healthy and safe work environment.